Corruption and Poverty Reduction in Zimbabwe: Evidence from a Symmetric and Asymmetric ARDL Co-integration Approach - Gonese, Dorcas (International Journal of Economics and Financial Issues, 2026)
The study examines the impact of corruption, measured by the Corruption Perception Index (CPI) and corruption control (coc), on poverty reduction in Zimbabwe from 2000 to 2022. The aim of this paper is twofold: firstly, to examine corruption's direct and conditional effects on poverty reduction; and secondly, to evaluate the asymmetric impact of corruption, institutional quality, and ICT on poverty reduction in Zimbabwe. The study employs the Autoregressive Distributed Lag (ARDL) and the non-linear Autoregressive Distributed Lag (NARDL) estimation techniques to assess the asymmetric effects of corruption on poverty reduction. The results indicate that corruption indicators have disparate direct effects on poverty reduction in Zimbabwe. Institutional quality is found to hinder poverty reduction, while ICT enhances it. Furthermore, the analysis shows that both institutional quality and ICT significantly moderate the relationship between corruption and poverty reduction. An asymmetric analysis demonstrates that both positive and negative shocks to corruption perception impede poverty reduction, as do the negative changes in the control of corruption. Moreover, the positive and negative shocks of institutional quality are shown to increase and reduce poverty reduction, respectively, while positive shocks of ICT enhance it. The findings provide a basis for policy recommendations.